Colistin susceptibility pattern of multi drug-resistant Escherichia coli from poultry farms in Malaysia - Khor, Shu Neng (2016)
Colistin is a critically important antibiotic in human medicine. However, the plasmid-mediated colistin resistance mechanism in animal and human was discovered widespread in China in 2015, and has since been detected in other countries at the time of writing. As poultry livestock industry is important in Malaysia, this study aimed to describe the colistin susceptibility pattern of multidrug-resistant Escherichia coli(MDR E.coli)from different poultry farms in Malaysia. With the cooperation of a private laboratory, data from 1st January 2014 to 1 December 2015 for 69 antimicrobial susceptibility profile of MDR E.coliwhich was subjected to antibiotic sensitivity testing by using Kirby-Bauer disk diffusion method was retrieved.The major antibiotic evaluated in this study was colistin.The data was analysed by using SPSS version20. Based on the results generated, MDRE.coli showed highest susceptibility to colistin(90%). This was followed by fosfomycin (57%). The MDR E.coli showed total non-susceptibility to amoxicillin/clavulanic acid, amoxicillin and tilmicosin. In addition, there is no significant association between colistin susceptibility pattern and both years or resistance pattern to other tested antibiotics. Prudent use of colistin in livestock is highly recommended to prevent spread of colistin resistance.